2019
DOI: 10.17547/kjsr.2019.27.1.46
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Job Stress, Burnout and Nursing Performance of Nurses in Comprehensive Nursing Care Service Wards and Nurses in General Wards

Abstract: Background: The purpose of this study was to compare job stress, burnout and nursing performance between nurses who work in comprehensive nursing care service wards and general wards. In addition we identified a correlation among job stress, burnout and nursing performance. Methods: The participants were 80 nurses (comprehensive nursing care service ward: 40, general wards: 40) and the data were collected using structured questionnaires to assess job stress, burnout and nursing performance. Results: There was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
3
7
0
2
Order By: Relevance
“…First, the mediation model revealed that in all nurses, work stress was found to have a direct effect on burnout; higher burnout was found when work stress was higher. These findings are consistent with those of previous studies, confirming the relationship between work stress and burnout in nurses (Choi et al, 2017; Kim, Park, & Seo, 2019). Additionally, there was an indirect effect of anger expression between work stress and burnout in the whole nurse model; anger‐in and anger‐control had indirect effects on burnout.…”
Section: Discussionsupporting
confidence: 93%
“…First, the mediation model revealed that in all nurses, work stress was found to have a direct effect on burnout; higher burnout was found when work stress was higher. These findings are consistent with those of previous studies, confirming the relationship between work stress and burnout in nurses (Choi et al, 2017; Kim, Park, & Seo, 2019). Additionally, there was an indirect effect of anger expression between work stress and burnout in the whole nurse model; anger‐in and anger‐control had indirect effects on burnout.…”
Section: Discussionsupporting
confidence: 93%
“…According to a previous study, nurses experience higher stress and more physical and psychosocial health problems compared with other professional groups; thus, the quality of nursing care and turnover is a concern [ 5 ]. Stress has a significant positive correlation with burnout, which decreases productivity and efficiency of nursing work and causes deterioration of nursing performance outcomes, impacting the ability to provide quality nursing care and causing loss to hospital management [ 3 , 6 ]. As a result, various efforts are being made to relieve the stress and burnout faced by nurses in their field and to improve nursing performance [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nurses are one of the professional groups with very high risk of burnout [ 6 , 15 ]. Nurses who experience burnout feel negative emotions and attitudes toward patients [ 18 ] and fail to concentrate on work, causing patient safety-related problems [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have explored the relationships between work stress, job satisfaction, and CS with BO and STS [9,24,25]. Many studies have linked job stress to burnout [26][27][28][29] and job satisfaction [27,30]. A prospective cohort study carried out by the Korea Nurses' Health Study (KNHS) among 10,305 nurses found a strong positive correlation between stress and burnout [31].…”
Section: Study Variablesmentioning
confidence: 99%